Potential for utilizing blended drainage water for irrigating west side, San Joaquin Valley pistachios - Ferguson L.; Sanden B.; Grattan S.; Reyes H.C.; Wilson C.; Cross E. (XI GREMPA Seminar on Pistachios and Almonds, 2001)
Our results through 1999 demonstrate that six sequential seasons of irrigation with 8 dS per m water produced no significant effect on marketable yield of trees grown on the four major commercial California pistachio rootstocks. Two sequential seasons of irrigation water with 12 dS per m significantly decreased yield as follows. In 1997, trees grown on UCB-1 rootstocks had a 19 per cent decrease in marketable yield and trees on Atlantica rootstocks a 14 per cent, trees on PGI and PGII rootstocks had no decrease in yield. In 1998, trees grown on UCB-1 rootstocks had a 49 per cent decrease, trees on Atlantica rootstocks a 19 per cent, trees on PGII an 18 per cent, and trees on PGI a 14 per cent decrease in marketable yield. In 1999, yields dropped sharply as a result of alternate bearing, making yield comparisons useless.
11. GREMPA Seminar on Pistachios and Almonds, 1999/09/01-04, Sanliurfa (Turkey)